Elaboration and validation of a diagrammatic scale to assess downy mildew severity in grapevine - Buffara,Cláudia Regina Scapin (2014)
The downy mildew, caused by Plasmopora viticola, is one of the most important grapevine (Vitis vinifera) diseases in Southern Brazil, causing defoliation and economic losses. The evaluation of disease severity is an important decision for adoption of strategies and tactics for disease control. Therefore, the objective of this work was to elaborate and to validate a diagrammatic scale to assess downy mildew severity in grapevine, respecting the limitations of visual acuity. The diagrammatic scale with seven levels of disease severity of 1, 3, 6, 12, 25, 50 and 75% was developed in two versions of black-and-white and color scale. The scales were tested and validated by eight raters with and without previous experience with grapevine downy mildew. The raters estimated the severity of 30 grapevine leaves with different downy mildew severity, with and without the use of the scales. Minimum, intermediate and maximum severity levels were collected according to Weber-Fechner's stimulus-response law. The accuracy and precision were analyzed by linear regression between the actual and the estimated severity. Actual severity was assessed with ASSESS(r) Program. The scales provided good levels of accuracy (means of 88%) and excellent levels of precision (means of 95%). The raters showed great precision and accuracy when used the diagrammatic scale. The color scale provided more precise and accurate estimates than the black-and-white scale. The scale proposed in this work presented appropriate applicability for downy mildew evaluation in grapevine.